Black Wattle Tannin As Steel Corrosion Inhibitor. (9th April 2012) - Peres, Rafael Silveira; Cassel, Eduardo; Azambuja, Denise Schermann
Abstract : In order to reduce the environmental impacts caused by chemical substances harmful to the environment and human health, the black wattle tannin can be used as an environmentally friendly corrosion inhibitor in acid and near neutral media. This paper provides information on the application of black wattle tannin as an inhibitor against the corrosion of carbon steel. The inhibition was evaluated using potentiodynamic polarization (PP) and electrochemical impedance spectroscopy (EIS) at room temperature in aerated 0.1 mol L −1 Na2 SO4 (pH 6.0 and 2.5). The black wattle tannin when used as a corrosion inhibitor is more effective at acidic pH, its efficiency being dependent on its concentration. At the higher pH value (pH 6.0), a blue-black film (ferric tannate) with a short-term protection against corrosion was formed in aerated aqueous solution. At pH 2.5, this blue-black film was not observed.